Use of prisms in ophthalmology: a review Part 1. The use of prisms in strabismus: historical background, methodologies and their outcomes - V.I. Serdiuchenko (Ukrainian Society of Ophthalmologists, 2020)
The paper points to the principle of prisms: if a prism is placed in front of the strabismic eye, images of objects impinging upon the peripheral retina are projected to the central pit, which creates optimal conditions for cooperation of both eyes and facilitates binocular vision. In strabismic eyes, prisms are used for the following purposes: measuring the angle of strabismus; determining if binocular vision or suppression scotoma is present; obtaining sensorial orthophoria with prisms and developing binocular vision; compensating for diplopia and correcting forced head rotation in paralytic strabismus; determining the maximum deviation and the amount of surgery when preparing a patient for surgery; and diploptic treatment of strabismus. The review is related also to the literature of the last fifty years on the outcomes of treating strabismic patients with Fresnel prisms. In particular, the paper presents the advantages of modified Fresnel prisms developed in Ukraine and the outcomes of treating strabismic patients with these prisms.